Urease of Enterohemorrhagic Escherichia coli: Evidence for Regulation by Fur and a trans-Acting Factor - Heimer, Susan R. (American Society for Microbiology, 2002)
Recent genomic analyses of Escherichia coli O157:H7 strain EDL933 revealed two loci encoding urease gene homologues (ureDABCEFG), which are absent in nonpathogenic E. coli strain K-12. This report demonstrates that the cloned EDL933 ure gene cluster is capable of synthesizing urease in an E. coli DH5α background. However, when the gene fragment is transformed back into the native EDL933 background, the enzymatic activity of the cloned determinants is undetectable. We speculate that an unidentified trans-acting factor in enterohemorrhagic E. coli (EHEC) is responsible for this regulation of ure expression. In addition, Fur-like recognition sites are present in three independent O157:H7 isolates upstream of ureD and ureA. Enzymatic assays confirmed a difference in urease expression of cloned EHEC ure clusters in E. coli MC3100Δfur. Likewise, interruption of fur in O157:H7 isolate IN1 significantly diminished urease activity. We propose that, similar to the function of Fur in regulating the acid response of Salmonella enterica serovar Typhimurium, it modulates urease expression in EHEC, perhaps contributing to the acid tolerance of the organism.